Aplikasi Web Question Answering Menggunakan Langchain OpenAI Tentang Peraturan Perundang-undangan Bidang Pendidikan - Saputra, Ikhsan Dwi; Harahap, Nazruddin Safaat; Agustian, Surya; Fikry, Muhammad; Oktavia, Lola (Journal of Computer System and Informatics (JoSYC), 2024)
In the rapid development of information technology over the past few years, the ease of accessing information has been one of the significant achievements. Artificial intelligence (AI) has emerged as a potential tool in bringing innovative solutions in various sectors of human life. This research aims to develop a web application capable of answering questions related to educational legislation using the LangChain framework and BERT model. The primary issue addressed is the complexity and volume of legal documents that are challenging for lay users to access and understand. The methodology involves converting legal documents from PDF to text, segmenting the text using LangChain, and evaluating system performance with BERTScore and ROUGE Score. The results indicate that BERTScore is superior in measuring the alignment between the system’s answers and reference answers, with some questions achieving a score of 100%. However, there are limitations, such as the manual effort required for document conversion and the substantial computational resources needed for text processing. This research significantly contributes to facilitating access and comprehension of educational legal documents and opens opportunities for further development with more advanced conversion techniques and AI models.